2016
DOI: 10.1016/j.antiviral.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

An avian influenza H5N1 virus vaccine candidate based on the extracellular domain produced in yeast system as subviral particles protects chickens from lethal challenge

Abstract: Highly pathogenic avian influenza is an on-going problem in poultry and a potential human pandemic threat. Pandemics occur suddenly and vaccine production must be fast and effective to be of value in controlling the spread of the virus. In this study we evaluated the potential of a recombinant protein from the extracellular domain of an H5 hemagglutinin protein produced in a yeast expression system to act as an effective vaccine. Protein production was efficient, with up to 200 mg purified from 1 L of culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…The vaccine based on this HA domain fully protected chickens from lethal infections by the highly pathogenic H5N1 virus (22). This time, in order to obtain the antigens with a native protein sequence, we excluded any affinity tags.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vaccine based on this HA domain fully protected chickens from lethal infections by the highly pathogenic H5N1 virus (22). This time, in order to obtain the antigens with a native protein sequence, we excluded any affinity tags.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that all human cells use this glycan moiety as a foundation to form complex glycans (21). Previously, we showed that immunization with the subunit vaccine based on the extracellular region of H5 hemagglutinin with deletion of the multibasic cleavage site fully protected chickens from lethal infections by the highly pathogenic H5N1 virus (22). We also demonstrated that such an antigen spontaneously oligomerized into spherical structures.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous results showed that the recombinant H5 protein encompassing residues from the extracellular domain adopted the correct three-dimensional structure required for oligomerization. Moreover, the H5 vaccine produced in Pichia cells proved to be protective for chickens challenged with a lethal dose of the highly pathogenic H5N1 virus [9]. Therefore, in this study, the transmembrane region and cytoplasmic tail of the H1 protein were also excluded.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of this study was to test an H1N1pdm09 influenza virus HA produced in a yeast expression system as a potential vaccine antigen. Our previous study showed that the H5 antigen produced in the P. pastoris cells is capable of inducing a specific immune response in mice [8, 10] and providing full protection in chicken [9]. Ease of preparation, low cost of production, and high immunogenicity of the yeast-derived antigen prompted us to test an H1N1pdm09 influenza virus antigen.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, two novel lines of influenza A virus H17N10 and H18N11 subtypes were detected in rectal swabs of the small yellow-shouldered bat and the flat-faced fruit-eating bat [ 46 ]. To date, only glycoprotein’s subtypes N1, N2 and H1, H2, H3 are known to have positively adapted to humans [ 47 ].…”
Section: Biochemistry and Mechanism Of Infectionmentioning
confidence: 99%